AN ANALYSIS OF TEACHER STYLE IN TEACHING ENGLISH LISTENING - Anggi Anggriani; Hanipah Nurrohmah (IKIP Siliwangi, 2018)
The title of this research is “An Analysis of Teacher Style in Teaching English Listening” at the tenth grade students of SMK Negeri 1 Bojong Purwakarta. The objective of this research is to find out style of teacher in teaching English listening skill at tenth grade of SMK Negeri 1 Bojong Purwakarta. Listening is one of the skills in English learning and it is required in curriculum for senior high school in Indonesia. In general, teaching listening is similar to other skills. The method of this research is descriptive qualitative method. The instrument used in this research is observation and questionnaire. The participant of this research is one of the English teacher of SMK Negeri 1 Bojong Purwakarta at tenth grade. The result of observations and questionnaire showed that teaching style used by the teacher in teaching English listening at tenth grade of SMK Negeri 1 Bojong Purwakarta are 90% teacher as expert, 80% teacher as formal authority, 67% teacher as demonstator, 95% teacher as facilitator, and 90% teacher as delegator. And based on the results of observation and questionnaire the researchers hope the teacher also pay more attention to the student in teaching English. Keywords: Listening Skill, Teaching Style